2021
DOI: 10.3389/fimmu.2021.662307
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of CXCL10 in Monitoring Response to Treatment in Leprosy Patients

Abstract: The treatment of multibacillary cases of leprosy with multidrug therapy (MDT) comprises 12 doses of a combination of rifampicin, dapsone and clofazimine. Previous studies have described the immunological phenotypic pattern in skin lesions in multibacillary patients. Here, we evaluated the effect of MDT on skin cell phenotype and on the Mycobacterium leprae-specific immune response. An analysis of skin cell phenotype demonstrated a significant decrease in MRS1 (SR-A), CXCL10 (IP-10) and IFNG (IFN-γ) gene and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Upregulation of CD8 antigen in reversal reactions has also been noted in leprosy/HIV co-infections (de Oliveira et al, 2013). Several studies revealed the upregulation of CXCL10 (IP10) in reactional states of leprosy (Chaitanya al., 2013;van Hooij et al, 2016;Ferreira et al, 2021). Expression of IP-10 is seen in many Th1-type inflammatory diseases, where it is thought to play an important role in recruiting activated T cells into sites of tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of CD8 antigen in reversal reactions has also been noted in leprosy/HIV co-infections (de Oliveira et al, 2013). Several studies revealed the upregulation of CXCL10 (IP10) in reactional states of leprosy (Chaitanya al., 2013;van Hooij et al, 2016;Ferreira et al, 2021). Expression of IP-10 is seen in many Th1-type inflammatory diseases, where it is thought to play an important role in recruiting activated T cells into sites of tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although, patients with psoriasis, rheumatoid arthritis with interstitial lung disease, viral meningitis, and other mycobacterial diseases like tuberculosis and sarcoidosis also have been discovered to express CXCL10. This suggest that CXCL10 is elevated in chronic inflammatory disease ( Makarem et al, 2024 ; Ferreira et al, 2021 ; Hungria et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%
“…Both TNF-α and IFN-γ have been found to attach to the macrophage cellular receptors in leprosy, resulting in creation of NO and free radicals that kill M. leprae ( de Sousa, Sotto & Quaresma, 2017 ). When pro-inflammatory conditions exist, a variety of cell types including leukocytes, monocytes, fibroblasts, activated neutrophils, epithelial cells, endothelial cells, mesenchymal cells, stromal cells, and keratinocytes release C-X-C motif chemokine ligand 10 or CXCL10, also known as interferon gamma induced protein (IP-10), in response to IFN-γ ( Makarem et al, 2024 ; Ferreira et al, 2021 ). However, an increase in CXCL10 is not always followed by an increase in IFN-γ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that PBMC from MB MDT-responders (MDT-R, with reduction of at least one log in BI after MDT) produced higher levels of CXCL10 in response to M. leprae when compared to cells from MDT-non-responders (MDT-NR, reduction lower than 1 log in BI after 12-doses MDT) MB patients (Ferreira et al, 2021). Here, we used host transcriptomic profiling by RNA-seq to explore differences in genes and pathways associated with a better response to treatment that could help suggest adjuvant or new and more effective antileprosy drugs.…”
Section: Introductionmentioning
confidence: 99%